A política externa brasileira ao longo do período Rio Branco (1902-1912): o olhar da imprensa e da diplomacia estadunidense e argentina - Szmidt, Daniel (Universidade do Vale do Rio dos Sinos, 2011)
Barao de Rio Brancos rising to the position of chancellor in 1902 determined a change of course for the Brazilian foreign policy. By executing a project which intended to recoup the national prestige, Rio Branco solved boundary litigations and used the leverage with the United States to increase Brazils influence in South America. The point of the present paper was to analyze how Brazil and its foreign relations policy were interpreted by sectors of the press and diplomats both from Argentina and the USA during the 10 years of Rio Branco´s tenure. In Argentina, newspapers as La Nación, La Prensa, El País, El Diario, La Razón, and El Sarmiento as well as the magazine Revista de Derecho, Historia y Letras, were all researched. As to the American view, the online files of The New York Times, the speeches of Elihu Root, during his trip to Brazil in 1906, and the works of the jurist and diplomat John Basset Moore were researched. The comparative analysis of these sources led us to the conclusion that in Argentina a significant part of the press considered Brazil as a threat to be contained, criticizing Brazils Foreign relation actions, whereas in the American view Brazil was an important ally and a relatively stable country in the Latin American context.
Keywords: Política externa brasileira; Argentina; Estados Unidos; Imprensa; Representações; Brazilian foreign policy; United States; Press; Representations; ACCNPQ::Ciências Humanas::História